Metformin alleviates lung-endothelial hyperpermeability by regulating cofilin-1/PP2AC pathway - Siddiqui, M. Rizwan; Reddy, Narsa M.; Faridi, Hafeez M.; Shahid, Mohd; Shanley, Thomas P. (Frontiers in Pharmacology, 2023)
Microvascular endothelial hyperpermeability is an earliest pathological hallmark in Acute Lung Injury (ALI), which progressively leads to Acute Respiratory Distress Syndrome (ARDS). Recently, vascular protective and anti-inflammatory effect of metformin, irrespective of glycemic control, has garnered significant interest. However, the underlying molecular mechanism(s) of metformin’s barrier protective benefits in lung-endothelial cells (ECs) has not been clearly elucidated. Many vascular permeability-increasing agents weakened adherens junctions (AJ) integrity by inducing the reorganization of the actin cytoskeleton and stress fibers formation. Here, we hypothesized that metformin abrogated endothelial hyperpermeability and strengthen AJ integrity via inhibiting stress fibers formation through cofilin-1-PP2AC pathway. Our in-vitro studies showed that metformin treatment attenuated thrombin-induced hyperpermeability, stress fibers formation, and the levels of inflammatory cytokines IL-6 and IL- in human lung microvascular ECs (human-lung-ECs). In exploring the mechanisms, we found that metformin mitigated Ser3-phosphorylation mediated inhibition of cofilin-1 in response to thrombin. Furthermore, genetic deletion of PP2AC subunit significantly inhibited metformin efficacy to mitigate thrombin-induced Ser3-phosphorylation cofilin-1, AJ disruption and stress fibers formation. We further demonstrated that metformin increases PP2AC activity by upregulating PP2AC-Leu309 methylation in human-lung-ECs. We also found that the ectopic expression of PP2AC prevented thrombin-induced Ser3-phosphorylation-mediated inhibition of cofilin-1 and endothelial hyperpermeability. Together, these data reveal the unprecedented endothelial cofilin-1-PP2AC signaling axis downstream of metformin in protecting against lung vascular endothelial injury and inflammation. Therefore, pharmacologically enhancing endothelial PP2AC activity may lead to the development of novel therapeutic approaches for prevention of deleterious effects of ALI on vascular ECs.